The Role of Psycholinguistics in School Methodology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article examines psycholinguistics in school teaching methods, using the English language as an example, the concept of “psycholinguistics” as a theory of speech activity. The author focuses on the goals and objectives of early teaching of foreign languages on the basis of exercises and games based on the school methods of teaching psycholinguistics.